2022
DOI: 10.5603/pjnns.a2022.0013
|View full text |Cite
|
Sign up to set email alerts
|

Different blood-brain-barrier disruption profiles in multiple sclerosis, neuromyelitis optica spectrum disorders, and neuropsychiatric systemic lupus erythematosus

Abstract: Aim of the study. To assess differences in BBB damage profiles by measuring serum levels of soluble vascular cell adhesion molecule-1 (sVCAM-1), soluble platelet endothelial cell adhesion molecule-1 (sPECAM-1), soluble intercellular adhesion molecule-1 (sICAM-1), and S100 calcium-binding protein B (S100B) in relapsing-remitting multiple sclerosis (RRMS), neuromyelitis optica spectrum disorders (NMOsd), and neuropsychiatric systemic lupus erythematosus (NPSLE) patients.Clinical rationale for the study. Blood-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…BBB dysfunction is an early event in MS, which is followed by immune cell infiltration and the extravasation of plasma proteins. How the BBB contributes to MS pathogenesis and progression is discussed elsewhere [ 46 , 220 , 221 , 222 , 223 ]. Nishihara et al [ 224 ] showed that different Th subsets had comparable migration rates through the BBB in a transwell setup under inflammatory conditions (mediated by TNF- and interferon- ).…”
Section: Disease-specific Modeling Of Neuroinflammationmentioning
confidence: 99%
“…BBB dysfunction is an early event in MS, which is followed by immune cell infiltration and the extravasation of plasma proteins. How the BBB contributes to MS pathogenesis and progression is discussed elsewhere [ 46 , 220 , 221 , 222 , 223 ]. Nishihara et al [ 224 ] showed that different Th subsets had comparable migration rates through the BBB in a transwell setup under inflammatory conditions (mediated by TNF- and interferon- ).…”
Section: Disease-specific Modeling Of Neuroinflammationmentioning
confidence: 99%
“…Chociaż przeciwciała przeciwko akwaporynie 4 (AQP4-IgG) uznawane są za swoisty marker NMOSD oraz istotny element patogenezy choroby i czynnik predykcyjny, proces diagnostyczny pozostaje trudny, szczególnie w przypadku pacjentów seronegatywnych [11]. Biomarkerem, który może okazać się pomocny w procesie diagnostycznym takich chorych jest miano MOG-Ab (ang.…”
Section: Patofizjologia Nmosdunclassified
“…acute disseminated encephalomyelitis). Funkcja MOG pozostaje niejasna, podobnie jak to czy MOG-Ab są patogenne, czy wtórne do wcześniejszego stanu zapalnego, niemniej jednak stały się one ważnym markerem w chorobach demielinizacyjnych [9,11].…”
Section: Patofizjologia Nmosdunclassified
“…Passage through the BBB is rigorously restricted through physical (intercellular and adherence junctions) and metabolic barriers [3]. BBB disruption is one of the key pathological processes involved in various diseases of the CNS [4,5]. Proinflammatory cytokines and disease-specific proteins (e.g.…”
mentioning
confidence: 99%